Edukacja etyczna jako fundamentalny element wychowania w środowisku akademickim - Kapias, Michał; Polok, ks. Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2012)
Global changes in the world enforce to undertake various transformations also in the area of higher education. The aim of academiceducation is not more preparing to work in particular occupation, but rather to form appropriate abilities which are useful at the labourmarket. This kind of education must embody overall, multi-aspect character, because it prepares to lifelong learning. Therefore creating“learning society” one should make an effort into axiological dimension of scientific-technical advance. One ought to take heed of humanelements of education and first of all of ethical issues. Practise shows that human relations bereft of transcend and ethic dimension,but concentrating only on financial economical goods, on profit, market and competition, don’t bring anyone happiness. Hence thereis an enormous demand in the academic community an ethical reflection. Thanks to it human being is not only improved in anthropologicaldimension, but also in social-economical aspect.